2010
DOI: 10.1016/j.jmps.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic multiscale models and measurements of self-heating under multiaxial high cycle fatigue

Abstract: a b s t r a c tDifferent approaches have been proposed to link high cycle fatigue properties to thermal measurements under cyclic loadings, usually referred to as ''self-heating tests.'' This paper focuses on two models whose parameters are tuned by resorting to self-heating tests and then used to predict high cycle fatigue properties. The first model is based upon a yield surface approach to account for stress multiaxiality at a microscopic scale, whereas the second one relies on a probabilistic modelling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 27 publications
(41 reference statements)
2
37
0
2
Order By: Relevance
“…The evolution of the average dissipated energy per cycle W d (determined for the 1 000 th cycle) as a function of the stress amplitude Σ a is plotted in figure 4. As already observed by several authors (Berthel et al, 2007;Mareau et al, 2009;Poncelet et al, 2010), the amount of energy which is dissipated into heat during one loading cycle increases with the stress amplitude. showed that the dissipated energy augmentation is associated with an increase of the plastic activity that can be correlated with the formation of persistent slip bands.…”
Section: Resultssupporting
confidence: 71%
“…The evolution of the average dissipated energy per cycle W d (determined for the 1 000 th cycle) as a function of the stress amplitude Σ a is plotted in figure 4. As already observed by several authors (Berthel et al, 2007;Mareau et al, 2009;Poncelet et al, 2010), the amount of energy which is dissipated into heat during one loading cycle increases with the stress amplitude. showed that the dissipated energy augmentation is associated with an increase of the plastic activity that can be correlated with the formation of persistent slip bands.…”
Section: Resultssupporting
confidence: 71%
“…The fatigue strength can vary from one specimen to another due to the microstructure variability (texture, grain morphology, phase, defect, etc.). To take into account the role of microstructural heterogeneities in multiaxial fatigue prediction, recent models have been developed in a probabilistic framework [3,4]. These models allowed to establish a relation between the microstructure components and the variability of the fatigue behavior using generally the weakest link hypothesis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to the development of these approaches, recent work by Altus (2006), Morel and Huyen (2008) and Poncelet et al (2010) have made it possible to take into account the role of microstructural heterogeneities in terms of multiaxial fatigue modelling. These models seek to account for the effect of the variability of the mechanical behaviour at the scale of the microstructure, as simply as possible.…”
Section: Introductionmentioning
confidence: 99%